Strategi Marketing Islam Moderat di Kalangan Kaum Muda Millenial - Khaidir, Piet Hizbullah (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
Although the scent of radicalism has been smelled since the beginning of the Reformation, research by the Setara Institute and the Wahid Institute-LSI on the exposure of millennial youth to radical extremist ideology still surprises us. In this study, the author will examine how moderate Islamic marketing strategies among millennials use library research and focus group discussion methods. The location of this research is Lamongan City because Lamongan has a special characteristic related to transnational radicalism-extremism movements. Lamongan needs to be re-detected, considering that the millennial generation who grew up in Lamongan City has a very strong habit of using the internet and participating in social religious activities through the internet and mosques and Rohis-Rohis at school. This study will focus on examining the millennial generation in Lamongan City. In the moderate Islamic marketing strategy among millennials, there are several aspects that can be optimized including an integrated curriculum for moderate Islamic education, strengthening the identity of moderate Islamic groups, moderating Islamic narratives on social media, and compiling a political vision for moderate Islamic groups.